Older LGBT+ health inequalities in the UK: setting a research agenda. Issue 5 (21st February 2020) - Westwood, Sue; Willis, Paul; Fish, Julie; Hafford-Letchfield, Trish; Semlyen, Joanna; King, Andrew; Beach, Brian; Almack, Kathryn; Kneale, Dylan; Toze, Michael; Becares, Laia
Abstract : Lesbian, gay, bisexual and trans+ (LGBT+) people report poorer health than the general population and worse experiences of healthcare particularly cancer, palliative/end-of-life, dementia and mental health provision. This is attributable to: (a) social inequalities, including 'minority stress'; (b) associated health-risk behaviours (eg, smoking, excessive drug/alcohol use, obesity); (c) loneliness and isolation, affecting physical/mental health and mortality; (d) anticipated/experienced discrimination and (e) inadequate understandings of needs among healthcare providers. Older LGBT+ people are particularly affected, due to the effects of both cumulative disadvantage and ageing. There is a need for greater and more robust research data to support growing international and national government initiatives aimed at addressing these health inequalities. We identify seven key research strategies: (1) Production of large data sets; (2) Comparative data collection; (3) Addressing diversity and intersectionality among LGBT+ older people; (4) Investigation of healthcare services' capacity to deliver LGBT+ affirmative healthcare and associated education and training needs; (5) Identification of effective health promotion and/or treatment interventions for older LGBT+ people, and subgroups within this umbrella category; (6) Development of an (older) LGBT+ health equity model; (7) Utilisation of social justice concepts to ensure meaningful, change-orientated data production which will inform and support government policy, health promotion and healthcare interventions.